Odpowiedzi

2010-02-28T20:29:20+01:00
6+(-4)+(-10) = 6-4-10 = 2-10 = -8
-4-(-9)-3 = -4+9-3 = 5-3 = 2
-16+7-28 = -9-28 = -37
-2-3*5 = -2-15 = -17
(-8):4-2 = -2-2 = -4
12:(-2)-(-3) = -6+3 = -3
(-2)³*3-25 = -8*3-25 = -24-25 = -49
(-15):3-5*(-1) = -5+5 = 0
3*(-7)-7*(-2) = -21+14 = -7
6*(-4)+5*(-9) = -24-45 = -69
(-18):9-(-27):(-1) = -2-27 = -29
2010-02-28T20:31:43+01:00
6+(-4)+(-10)=-8
-4-(-9)-3=2
-16+7-28=-9-28=-37
-16+7-28=-9-28=-37
-2-3x5=-2-15=-17
(-8):4-2=-2-2=-4
12:(-2)-(-3)=-6+3=-3
(-2) do potęgi 3 x 3-25 <-- tego nie obliczę, bo nie wiem czy tu jest "+" czy "-"
(-15):3-5x(-1)= -5+5=0
3x(-7)-7x(-2)=-21+14=-7
6x(-4)+5x(-9)=-24-45=-69
(-18):9-(-27):(-1) =-2-27=-29

2010-02-28T21:02:08+01:00
+ i - = -
- i - = +

6+(-4)+(-10) = 6 - 4 - 10 = 2 - 10 = -8
-4-(-9)-3 = -4 + 9 - 3 = 5 - 3 = 2
-16+7-28 = -16 + 7 - 28 = -9 - 28 = -37
-2-3x5 = -2 -3 x 5 = -2 -15 = -17
(-8):4-2 = -8 : 2 = -4
12:(-2)-(-3) = 12 : -2 + 6 = -6 + 3 = -3
(-2) do potęgi 3 x 3-25 = -6 x 3 - 25 = -18 - 25 = -43
(-15):3-5x(-1) = -15 : 3 - 5 x -1 = -5 -5 x -1 = -5 + 5 = 0
3x(-7)-7x(-2) = 3 x -7 -7 x -2 = -21 -7 x -2 = -21 + 14 = 7
6x(-4)+5x(-9) = 6 x -4 + 5 x - 9 = -24 + 5 x - 9 = - 24 - 45 = -69
(-18):9-(-27):(-1) = -18 : 9 + 27 : -1 = -2 + 27 = 25 : -1 = -25